2012
DOI: 10.1111/j.1440-1681.2011.05623.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and the regulation of endothelial function in physiological and pathological conditions

Abstract: Obesity and the accompanying metabolic syndrome are among the most important causes of cardiovascular pathologies associated with endothelial dysfunction, such as arterial hypertension and atherosclerosis. This detrimental effect of obesity is mediated, in part, by excessive production of the adipose tissue hormone leptin. Under physiological conditions leptin induces endothelium-dependent vasorelaxation by stimulating nitric oxide (NO) and endothelium-derived hyperpolarizing factor (EDHF). Leptin activates en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 79 publications
(180 reference statements)
1
71
0
3
Order By: Relevance
“…It may lead to membrane permeability, fluidity and integrity changes, which may eventually result in severe cytotoxicity. 10,25 The obese patients in our study showed high TBARS levels before bariatric surgery compared to the control group. This suggests that the patients were predisposed to develop many diseases, as well as to face accelerated aging, because the cytotoxicity caused by lipid oxidation favors uncontrolled cell growth and/or cell death.…”
Section: Figurementioning
confidence: 86%
See 2 more Smart Citations
“…It may lead to membrane permeability, fluidity and integrity changes, which may eventually result in severe cytotoxicity. 10,25 The obese patients in our study showed high TBARS levels before bariatric surgery compared to the control group. This suggests that the patients were predisposed to develop many diseases, as well as to face accelerated aging, because the cytotoxicity caused by lipid oxidation favors uncontrolled cell growth and/or cell death.…”
Section: Figurementioning
confidence: 86%
“…24 Furthermore, excess of body fat also affects the mitochondrial metabolism and promotes hyperleptinemia, thus favoring the occurrence of oxidative stress. [8][9][10] The formation of lipid peroxidation (LPO) products is one of the consequences from oxidative stress. It may lead to membrane permeability, fluidity and integrity changes, which may eventually result in severe cytotoxicity.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Êð³ì òîãî, íà ñó÷àñíîìó åòàï³ âèâ÷àºòüñÿ ïîøêîäaeóþ÷èé âïëèâ ëåïòèíó íà åíäîòåë³é ñó-äèí, ùî ïîëÿãຠó çíèaeåíí³ ðåëàêñàö³¿ àðòåð³é, ïîñèëåíí³ êàëüöèô³êàö³¿ ñóäèí ³ ó ïîòåíö³þâàíí³ ïðîòðîìáîòè÷íî¿ àãðåãàö³¿ òðîìáîöèò³â øëÿõîì âçàºìî䳿 ì³ae ëåïòèíîì ³ éîãî ðåöåïòîðàìè íà òðîìáîöèòàõ [37,38]. Âñå öå äîçâîëÿº ââàaeàòè ã³ïåðëåïòèíåì³þ îäíèì ³ç ÷èííèê³â, ùî ñïðèÿ-þòü ðîçâèòêó àòåðîñêëåðîòè÷íèõ ïîøêîäaeåíü ñóäèí é àñîö³éîâàíèõ ³ç íèìè çàõâîðþâàíü ñåð-öåâî-ñóäèííî¿ ñèñòåìè.…”
Section: роль ліпоцитокінів у патогенезі метаболічного синдромуunclassified
“…Leptin, produced by white adipose tissue in amounts proportional to energy stores, not only inhibits food intake and increases energy expenditure, but also has many e ects on peripheral tissues including the cardiovascular system (3,4). In physiological conditions leptin has no e ect on blood pressure because induces balanced stimulation of sympathetic nervous system (SNS) and endothelium-dependent vasorelaxation (5). Conditions of chronic hyperleptinemia such as obesity, metabolic syndrome or type 2 diabetes are associated with selective leptin resistance; that is pressor SNS-dependent e ect of leptin is preserved whereas its vasodilating e ect is impaired (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%